Environmental responses of carbon dioxide and methane fluxes of subarctic ecosystems in Northern Finland - Heiskanen, Lauri (Ilmatieteen laitos, 2023)
The subarctic landscape consists of diverse ecosystems, each having a multitude of biological processes controlling the carbon (C) cycle. Thus, the ecosystem-atmosphere exchange of carbon dioxide (CO2) and methane (CH4) can display substantial temporal and spatial variation. In this thesis, the objective was to study the C flux responses to changing environmental conditions on the plant community, ecosystem and landscape level. The study sites included fen, upland pine forest, pine bog and lake ecosystems and a mountain birch foresttundra ecotone. The CO2 and CH4 fluxes were measured with the eddy covariance and flux chamber methods during two meteorologically contrasting years. The fen acted as a small annual CO2 sink and an effective CH4 source to the atmosphere, while the pine forest was an effective CO2 sink. The emissions of CO2 and CH4 were sevenfold from the organic compared to the mineral sediment lake. The annual pine bog CO2 sink was estimated to be between the fen and forest sinks. The C fluxes of the four main plant community types (PCTs) of the flark-string microtopography continuum at the fen were controlled by vegetation composition, water table and meteorology. The driest PCTs had larger ecosystem respiration and gross photosynthesis than the wet ones. The three wettest PCTs contributed roughly equally to the total CH4 emissions of the fen, while the emissions from the driest PCT were minor. The fen C fluxes differed between the measurement years during two distinct periods: the warmer-than-average spring in 2018 and a heatwave and drought event in July 2018. The warm spring increased CO2 uptake, while the drought decreased both CO2 uptake and CH4 emissions. The drought also decreased the CO2 uptake of the other terrestrial ecosystems including the birch ecotone. The pine forest CO2 fluxes were affected by the rainy summer in 2017 by increasing the respiration, and a cold spell in autumn 2018, which decreased respiration. Since the post-glacial peatland initiation, peatland expansion and ...